The current status of resistance to alpha-cypermethrin, ivermectin, and amitraz of the cattle tick (Rhipicephalus microplus) in Ecuador. - Richar Rodríguez-Hidalgo; Ximena Pérez-Otáñez; Sandra Garcés-Carrera; Sophie O Vanwambeke; Maxime Madder; Washington Benítez-Ortiz (PLoS ONE, 2017)
Rhipicephalus microplus is widely distributed in tropical and subtropical areas of the world where livestock is a principal activity with great veterinary and economic importance. In Ecuador, this hematophagous ectoparasite has been observed between 0 and 2600 masl. One of the main tick control measures is the use of acaricides, which have been indiscriminately used worldwide and in Ecuador. In this country, no studies on acaricide resistance in Rhipicephalus microplus have been published. The current study aims to characterise the level of resistance of R. microplus against three main acaricides commonly used in Ecuador i.e. amitraz, alpha-cypermethrin and ivermectin to determine the level and pattern of dose-responses for R. microplus in 12 field populations (farms). The level of acaricide resistance was evaluated using three different bioassays: adult immersion test (AIT), larval package test (LPT) and larval immersion test (LIT), as recommended by the FAO. The predictive dose-responses were analysed by binomial logistics regression of the larval survival rate (resistance). In general, we found resistance of 67% for amitraz; 50% for alpha-cypermethrin and from 25 to 42% for ivermectin in the twelve field populations analysed. Resistance levels were studied in larval and adult bioassays, respectively, which were slightly modified for this study. For larval bioassays based on corrected mortality i.e. high (above 51%), medium (21-50%) and low (11-20%) resistance, percentages less than 10% were considered as susceptible. For the adult test, two resistance levels were used i.e. high (more than 76%) and medium (51 to 75%) resistance. Percentages lower than 50% were considered as susceptible. In this context, for larval bioassays, amitraz showed 21%, 38% and 8% for high, medium and low resistance, respectively. Alpha-cypermethrin presented 8%, 4 and 38% for high, medium and low resistance, respectively. Ivermectin presented 8%, 25% and 8% for high, medium and low resistance, respectively. For adult tests with amitraz 50% and 17% of the field populations showed average and high resistance, with evidences of average resistance to alpha-cypermethrin in 50% of the samples and average resistance against ivermectin in 25% of the farms. No statistical difference amongst the three bioassays was found and acaricide resistance was confirmed by logistic regression analysis; hence resistance (dose-responses) in each field populations differed, depending on the choice of the acaricide, frequent usage, frequency of treatment and farm management. The effective estimated dose needed to eliminate 99% of ticks is higher than dose recommended by the manufacturer. In conclusion, amitraz showed the highest resistance followed by ivermectin and alpha-cypermethrin and reveals differences on resistance in each individual field population. This information is important in order to establish the monitoring of resistance on each farm individually, contributing to the rational use of acaricides included in an integrated control program for R. microplus.